Charged particle therapy for cancer: the inheritance of the Cavendish scientists? - Jones, B; Dale, R; Cárabe-Fernández, A (2009)
The history of developments in atomic physics and its applications follows the decisive input provided by Maxwell and subsequent discoveries by his successors at the Cavendish Laboratory. In medicine the potential applications of particle physics (with the notable exception of the electron) were unfortunately delayed by the disappointing experiences with neutron therapy, which produced long-term scepticism. Neutrons are not appropriate for cancer therapy because not only their physical dose distributions offer no advantages over X-rays, but also their biological dose distributions are worse. The much improved dose distributions achieved with charged particles offer real prospects for better treatment outcomes because of the large reduction in the volume of unnecessarily irradiated tissue in many situations. Charged particle therapy is relatively new and can be applied with increasing confidence due to advances in radiology and computing, but at present there are insufficient numbers of treatment facilities to produce statistically powerful studies to compare treatment outcomes with those of X-rays. Considerable progress has been achieved in Japan and Germany with pilot studies of carbon ions but their efficacy compared with protons needs to be tested: in theory carbon should be better for intrinsically radio-resistant and for the most hypoxic tumours. The optimisation of proton and ion beam therapy in clinical practice remains to be achieved, but there are good scientific reasons why these modalities will be preferred by patients and their physicians in the future. Regrettably, despite hosting many of the momentous discoveries that enabled the development of charged particle therapy, the UK is slow to adopt and implement this very important form of cancer treatment.